“Without it, I am not sure I would still be here”: a mixed methods service evaluation for online EMDR trauma therapy in a primary care network in England - Kaptan, Safa Kemal; Dernedde, Carsten; Dowden, Tilda; Akan, Ayşe (Frontiers in Psychiatry, 2023)
Introduction: Psychological services are typically offered via specialized mental health services, which are often overwhelmed with long waitlists. To address this need and provide patients with a service characterized by shorter waiting times and increased accessibility, online Eye Movement Desensitization and Reprocessing (EMDR) was established in the North Norfolk 4 Primary Care Network. Methods: This article presents this service's collaborative funding, development and outcomes within local GP surgeries. It constitutes a mixed-method service evaluation encompassing the future of EMDR in primary care services. Additionally, it includes the assessment of anxiety, depression, and PTSD symptoms as well as work and social adjustment in a cohort of 83 patients alongside a Thematic Analysis involving eighteen patients and six GPs. Results: The evaluation showed high completion and attendance among service users. Quantitative scores combined with qualitative feedback from patients and practitioners highlight the potential impact of EMDR therapy on General Practice and its broader provision of trauma-focused therapies. The most significant improvements were observed in anxiety and depression scores. Thematic Analysis indicated that the patients found the service helpful, labeling it as a “life-saver”. They also discussed why they found the service effective; some also wished the service had been available earlier. Discussion: Findings underscore the potential of EMDR and online EMDR as an accessible and effective approach within primary care settings. The assessments showed an elevated level of access and attendance among service users. Therefore, it is recommended that timely EMDR services be extended through primary care networks.